Application of Building Integrated Photovoltaic (BIPV) in Net-Zero Energy Buildings (NZEBs) - Jiashu Kong; Yitong Dong; Aravind Poshnath; Behzad Rismanchi; Pow-Seng Yap (Energies, 2023)
Global energy consumption has led to concerns about potential supply problems, energy consumption and growing environmental impacts. This paper comprehensively provides a detailed assessment of current studies on the subject of building integrated photovoltaic (BIPV) technology in net-zero energy buildings (NZEBs). The review is validated through various case studies, which highlight the significance of factors such as building surface area to volume ratio (A/V), window-wall ratio (WWR), glass solar heating gain coefficient (SHGC), and others in achieving the NZEBs standards. In addition, this review article draws the following conclusions: (1) NZEBs use renewable energy to achieve energy efficiency and carbon neutrality. (2) NZEBs implementation, however, has some limitations, including the negligence of indoor conditions in the analysis, household thermal comfort, and the absence of an energy supply and demand monitoring system. (3) Most researchers advise supplementing facade and window BIPV as solely roofing BIPV will not be able to meet the building’s electricity usage. (4) Combining BIPV with building integrated solar thermal (BIST), considering esthetics and geometry, enhances outcomes and helps meet NZEB criteria. (5) BIPV designs should follow standards and learn from successful cases. However, to ascertain the long-term reliability and structural integrity of BIPV systems, a comprehensive study of their potential degradation mechanisms over extended periods is imperative. The review paper aims to examine BIPV applications in-depth, underscoring its pivotal role in attaining a net-zero energy benchmark.